Optical fiber tip sensor for glucose-adulterated honey detection - Nazirah Mohd Razali; Aimi Najwa Mazlan; Mohammad Farizuddin Salebi; Habibah Mohamed; Sumiaty Ambran (Universitas Ahmad Dahlan, 2019)
Honey, a natural sweet substance and also a high-value foodstuff has been a target for adulteration. This paper reports the early stage development of optical fiber tip sensor using a standard single mode fiber for adulterated honey detection. The development of simple, sensitive and low-cost sensor for direct detection of adulterated honey is a considerable interest in this context. A pure stingless bee honey was mixed with glucose adulterant at different volume ratios for the adulteration process. By changing this chemical composition, the refractive index of the adulterated honey varied and Fresnel reflection occured at the interface between the fiber tip and the adulterated honey solution also changed. The average sensitivity achieved by this sensor is 0.29 dBm/% with linear regression value up 0.97. This shows that, the sensor has a potential in adulterated honey detection.